2002
DOI: 10.3758/bf03195786
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tonal context and timbral variation on perception of pitch

Abstract: Pitch and timbre are two of the building blocks of music. Variations in pitch lead to a melodic line, whereas variations of timbre are usually heard as different instrumentations. Do pitch and timbre interact? Listening to an orchestra, one can hear a continuous melody being played when different instruments switch off playing separate parts of this melody, even if each note of the melody is played by a different instrument, a compositional style called klangfarbenmelodieor hocket. A more striking demonstratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 23 publications
10
99
1
Order By: Relevance
“…Previous research has indicated that timbre can affect judgments of whether one tone is higher or lower than another (Singh & Hirsh, 1992) and whether two tones differ in pitch (Warrier & Zatorre, 2002), but these effects were observed only for very small intervals involving tones that differed in fundamental frequency by 4% or less. Indeed, Warrier and Zatorre speculated that spectral shape is unlikely to affect pitch judgments when pitches differ in fundamental frequency by more than 4%.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous research has indicated that timbre can affect judgments of whether one tone is higher or lower than another (Singh & Hirsh, 1992) and whether two tones differ in pitch (Warrier & Zatorre, 2002), but these effects were observed only for very small intervals involving tones that differed in fundamental frequency by 4% or less. Indeed, Warrier and Zatorre speculated that spectral shape is unlikely to affect pitch judgments when pitches differ in fundamental frequency by more than 4%.…”
Section: Discussionmentioning
confidence: 92%
“…The spectra of the dull and bright timbres (modeled after those used by Warrier & Zatorre, 2002) are represented in Figure 1. The energy in the dull timbre was weighted in the lower partials, and the energy in the bright timbre was weighted in the higher partials so that the normalized spectral centroid (i.e., f c /f 0 , where f c is the amplitude-weighted mean of the frequency spectrum and f 0 is the fundamental frequency) of the dull timbre was lower than that of the bright timbre.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the related condition with the expected tonic target, pitch perception should be facilitated, in comparison with the less related condition with the less stable, less expected subdominant target. In Experiment 1, we used ratings of degree of mistuning (proposed by Warrier & Zatorre, 2002). In Experiment 2, we used a speeded reaction time task requiring binary judgments of mistuning.…”
Section: Tonal Expectationsmentioning
confidence: 99%
“…However, as smaller sets of intervals are used, the chances of obtaining musical phrases with a strong tonal identity would be higher. This gives rise to the question of whether musical context (which can significantly improve pitch judgements [10]) is a desirable factor in a display of numerical information or if, on the contrary, the sense of expectation of musical events that might arise [11] could interfere with the objective exploration of numerical information.…”
Section: Cognitive Limitations On Usable Display Resolutionmentioning
confidence: 99%